2021
DOI: 10.1007/s10010-021-00460-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a wind turbine gearbox virtual load sensor using multibody simulation and artificial neural networks

Abstract: A current development trend in wind energy is characterized by the installation of wind turbines (WT) with increasing rated power output. Higher towers and larger rotor diameters increase rated power leading to an intensification of the load situation on the drive train and the main gearbox. However, current main gearbox condition monitoring systems (CMS) do not record the 6‑degree of freedom (6-DOF) input loads to the transmission as it is too expensive. Therefore, this investigation aims to present an approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…On the other hand, solutions that aim to indirectly or virtually sense transmission input loads face a different challenge of collecting sufficiently representative data during WT operation to develop and validate their solutions [ 8 ]. Azzam et al addressed this need by providing a methodology for generating the necessary data for virtual load sensor development using multibody simulations (MBS) of a Vestas V52 WT model subjected to simulated wind fields according to IEC 61400-1 [ 9 ]. The authors demonstrated that MBS simulations can be used to significantly reduce the resources needed during development of WT virtual load sensors by providing a more flexible, less costly alternative to physical measurement campaigns as a data source for virtual sensor prototyping.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, solutions that aim to indirectly or virtually sense transmission input loads face a different challenge of collecting sufficiently representative data during WT operation to develop and validate their solutions [ 8 ]. Azzam et al addressed this need by providing a methodology for generating the necessary data for virtual load sensor development using multibody simulations (MBS) of a Vestas V52 WT model subjected to simulated wind fields according to IEC 61400-1 [ 9 ]. The authors demonstrated that MBS simulations can be used to significantly reduce the resources needed during development of WT virtual load sensors by providing a more flexible, less costly alternative to physical measurement campaigns as a data source for virtual sensor prototyping.…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, we address this need by presenting a methodology for sensor screening during the data-scarce virtual sensor design phase prior to real-world testing. Using the methodology recently published by Azzam et al [ 9 ], simulated wind fields covering a variety of operating conditions were applied to an MBS WT model to generate a time series of displacements, misalignments, and other parameters at various locations in the WT drivetrain. Using these simulated data, the methodology presented in this paper is intended to prioritize candidate sensors prior to real-world testing in order to (1) reduce the number of sensors required and (2) enhance the utility of the subsequent instrumentation and real-world testing phases, which were not repeatable in this project due to resource constraints.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations